Mewujudkan Lingkungan Pendidikan Berbasis Al-Qur’an - Rahman, Arif; ., Fahrudin; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2024)
A holistic educational paradigm can be realized through the integration of the educational environment with the elements of holistic totality in the Qur'an. This is based on the Qur'an's instructions regarding the elements of the environment. So that it can form a human being who is moral and beneficial to fellow humans and the environment. The view of the Qur'an that is the basis of the author's argument, basically humans since they are in the womb already have several potentials, and the educational environment in the Qur'an is comprehensive and integrated, covering all fields of knowledge, and is oriented towards the afterlife. This article uses qualitative methods. In discussing the interpretation of the Qur'an, the maudhu'i (thematic) method has been chosen in this research in order to find a comprehensive concept about the educational environment from the perspective of the Qur'an, and its use. qualitative methods to produce descriptive data whose results are presented in qualitative form. In addition, this research is based on library studies, because the data are in the form of verses of the Qur'an and authoritative interpretation books, and various written materials published in the form of books, journals, articles, websites, software. , magazines, and proceedings that are directly or indirectly related to the research. Therefore, this book falls into the qualitative research type.